2017
DOI: 10.1515/jim-2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy in Wound Healing

Abstract: Wound healing is a complex restorative process of the altered cutaneous tissue, which is impaired by numerous local and systemic factors, leading to chronic non-healing lesions with few efficient therapeutic options. Stem cells possess the capacity to differentiate into various types of cell lines. Furthermore, stem cells are able to secrete cytokines and growth factors, modulating inflammation and ultimately leading to angiogenesis, fibrogenesis, and epithelization. Because of their paracrine activity, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…During wound healing, MSCs take part in all stages of this process and were proven to persist at the wound site even after the completion of healing (Pratheesh et al, 2017). They coordinate the inflammatory process, modulate fibrosis and reduce scarring, as they show strong immunomodulatory and immunoregulatory characteristics demonstrated by release of cytokines, chemokines and growth factors (Hu et al, 2014;Mester et al, 2017;Ren et al, 2008). It is reported, that human MSCs release over 30 biomolecules, that promote wound healing (Hwang et al, 2009).…”
Section: 2mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…During wound healing, MSCs take part in all stages of this process and were proven to persist at the wound site even after the completion of healing (Pratheesh et al, 2017). They coordinate the inflammatory process, modulate fibrosis and reduce scarring, as they show strong immunomodulatory and immunoregulatory characteristics demonstrated by release of cytokines, chemokines and growth factors (Hu et al, 2014;Mester et al, 2017;Ren et al, 2008). It is reported, that human MSCs release over 30 biomolecules, that promote wound healing (Hwang et al, 2009).…”
Section: 2mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Stem cells possess characteristics like pluripotency and self-renewing properties [83]. These cells can secrete immunomodulatory cytokines to promote and coordinate angiogenesis, cell proliferation, and tissue regeneration [5]. Generally, stem cells resemble other mature cells but have no unique morphologic feature [5].…”
Section: Features Of Stem Cellsmentioning
confidence: 99%
“…The field of cell therapy has been enjoying a period of considerable activity and progress in the last decade [1]. Stem cell therapy has emerged as a viable alternative for the treatment of complex pathologies and tissue regeneration [5]. The challenge has moved on to harness the potential of stem cells for therapeutic uses and more research [1].…”
Section: Introductionmentioning
confidence: 99%
“…Adult HFSCs are more accessible, because they are not tumorigenic and have the immunomodulatory capacity [ 5 , 6 ] . HFSCs were found to contribute to wound healing after skin injury by migration and differentiation into epidermal cells [ 7 ] . Studies have shown strong multipotency of bulge stem cells, where they were attracted to differentiate into neurons, glial cells, keratinocytes, melanocytes, and mesenchymal cells; also, they were detected to contribute to angiogenesis [ 8 - 12 ] .…”
Section: Introductionmentioning
confidence: 99%